Anticancer Activity of Rosella Flowers (Hibiscus Sabdariffa l.) In HepG2 cells - Viani Anggi; Recky Patala; Arfiah Arfiah; Niluh Puspita Dewi (Jurnal Penelitian Pendidikan IPA, 2023)
The natural ingredients of rosella flowers have the potential as natural anti-cancer and chemopreventive agents, contain secondary metabolite compounds with cancer therapeutic mechanisms with inhibiting and killing cancer cells and their development through inhibition of apoptosis (cell death program) and in vitro inhibited cell flow. The study aims to identification of secondary metabolite compounds and also determine the cytotoxic activity of ethanol extract from the rosemary plant against HepG2 cancer cells. This study used by identification of secondary metabolite compounds of ethanol extract from the rosemary plant (Hibiscus sabdariffa L.) and the cytotoxicity test used with MTT assay on HepG2 liver cancer cells with a test concentration series of 12,5; 25; 50; 100; 200; 250; 500 and 1000 Âµg/ml. : The results showed the secondary metabolite compounds of rosella flowers have flavonoids, alkaloids, saponins and tannins and data of 50% cell growth inhibition activity, which was showed that rosella flower had IC50 values 629,919 Î¼g/mL. The ethanol extract of rosella flowers have activity on HepG2 cells growth inhibition had considered moderately active anticancer activity